Solve 2t-3(t+8)=-(1-4t)+10 for t. Simplify all fractions or roun

Antinazius 2021-11-16 Answered
Solve \(\displaystyle{2}{t}-{3}{\left({t}+{8}\right)}=-{\left({1}-{4}{t}\right)}+{10}\) for t. Simplify all fractions or round decimals to two places.

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more

Plainmath recommends

  • Ask your own question for free.
  • Get a detailed answer even on the hardest topics.
  • Ask an expert for a step-by-step guidance to learn to do it yourself.
Ask Question

Expert Answer

Uersfeldte
Answered 2021-11-17 Author has 1472 answers
Step 1
Given, \(\displaystyle{2}{t}-{3}{\left({t}+{8}\right)}=-{\left({1}-{4}{t}\right)}+{10}\)
\(\displaystyle{2}{t}-{3}{t}-{24}=-{1}+{4}{t}+{10}\)
\(\displaystyle-{t}-{24}={4}{t}-{1}+{10}\)
Step 2
\(\displaystyle-{t}-{24}={4}{t}+{9}\)
\(\displaystyle-{t}-{4}{t}={24}+{9}\)
\(\displaystyle-{5}{t}={33}\)
\(\displaystyle{t}={\frac{{-{33}}}{{{5}}}}\)
\(\displaystyle{t}=-{6}\cdot{6}\)
Have a similar question?
Ask An Expert
0
 

Expert Community at Your Service

  • Live experts 24/7
  • Questions are typically answered in as fast as 30 minutes
  • Personalized clear answers
Learn more
...